2015
DOI: 10.1002/jor.22972
|View full text |Cite
|
Sign up to set email alerts
|

Single intra‐articular dexamethasone injection immediately post‐surgery in a rabbit model mitigates early inflammatory responses and post‐traumatic osteoarthritis‐like alterations

Abstract: Despite surgical reconstruction of the anterior cruciate ligament, a significant number of patients will still develop posttraumatic osteoarthritis (PTOA). Our objective was to determine if mitigating aspects of the acute phase of inflammation following a defined knee surgery with a single administration of a glucocorticoid could prevent the development of PTOA-like changes within an established rabbit model of surgically induced PTOA. An early and late post-surgical time-point was investigated in this study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 33 publications
4
87
0
Order By: Relevance
“…Although this was not a major aim and this study was underpowered to demonstrate the absence of differences, effects of TAA bolus injections in OA joints compared to non‐treated joints, in contrast to the effects of the extended presence of TAA, are supported by various in vivo and clinical studies. Post‐surgical injection of the corticosteroid dexamethasone for inhibition of acute inflammation in a rabbit model of surgically induced OA showed no side effects (Heard et al, ; Huebner, Shrive, & Frank, ). In patients, corticosteroids have been intravenously administered perioperatively and post‐operatively during ACL repair surgery and orally afterwards to reduce inflammation and pain, without complications (Dahl, Spreng, Waage, & Raeder, ; Vargas & Ross, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this was not a major aim and this study was underpowered to demonstrate the absence of differences, effects of TAA bolus injections in OA joints compared to non‐treated joints, in contrast to the effects of the extended presence of TAA, are supported by various in vivo and clinical studies. Post‐surgical injection of the corticosteroid dexamethasone for inhibition of acute inflammation in a rabbit model of surgically induced OA showed no side effects (Heard et al, ; Huebner, Shrive, & Frank, ). In patients, corticosteroids have been intravenously administered perioperatively and post‐operatively during ACL repair surgery and orally afterwards to reduce inflammation and pain, without complications (Dahl, Spreng, Waage, & Raeder, ; Vargas & Ross, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the effects of glucocorticoids are dependent on the dose, frequency and duration of administration: large doses of corticosteroids have shown detrimental effects on cartilage structure, chondrocytes and subchondral bone (Wernecke et al , 2015). Only two reports were found that show chondroprotective effects with high Dex dose (Heard et al , 2015) and high frequency (Huebner et al , 2014) in a bone drill hole model of rabbit PTOA. A recent study by Flexion (Kumar et al , 2014) shows that intra-articular injection of clinically equivalent doses of triamcinolone in healthy beagle dogs (2, 6 and 19 mg) causes significant GAG loss that started 3 d after IA injection and peaked at 4–6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…steroid-induced arthropathy (steroid arthropathy) (44). The principle of steroid-induced arthropathy has not been in vivo 31: 69-78 (2017) 74 elucidated in detail, but steroid therapy is very effective as a treatment of acute OA (44,45,46). However, steroid treatment should be used with care in terms of time, niche, and optimum dose.…”
Section: Discussionmentioning
confidence: 99%